Amazoniana, transzamazônia, transarte: a geoestética - PRADO, Alcidean Augusto Brasil (Universidade Federal do Pará, 2018)
The Amazoniana, Transzamazônia, Transarte: Geoaesthetics will address questions about the position of the image in the Amazon, the place of matter in the region, the place of time in the Amazon. As these cycle times between image space, the territory of matter and entropy are given in the Amazon, it is what will decide when and how come the cycles of Amazoniana. Supported the research object, the Amazon project, place the Experiência¹. You begin to think the region by the project substrate, Amazoniana Collection of Art, to get to the Amazon as larger object to be investigated in the compilation of the four visual tests, which are subdivided for seven mônadas². Leaving for the Amazon by questions raised by Amazoniana. In order to bring the light effects and states of the region on aesthetic issues, image and art, to discuss areas of visuality in the development of the Amazon, from a question: "Where does the image in the Amazon?".